Burden of Interpandemic Influenza in Children Younger than 5 Years: A 25‐Year Prospective Study - Kathleen M. Neuzil; Yuwei Zhu; Marie R. Griffin; Kathryn M. Edwards; Juliette Thompson; Sharon J. Tollefson; Peter F. Wright (2002)
Many respiratory viruses cause morbidity in young children, but a licensed vaccine and effective oral therapy are available only for influenzavirus. To determine the incidence of laboratory-confirmed influenza illness, we prospectively followed up 1665 healthy children aged <5 years who were enrolled in the Vanderbilt Vaccine Clinic at some point from 1974 through 1999. Viral cultures were obtained when the children presented with clinical illness. The isolation of influenzavirus was associated with an estimated 95 health care visits for children with symptoms of influenza, 46 episodes of acute otitis media, and 8 episodes of lower respiratory tract disease per 1000 children yearly. Rates of acute otitis media and lower respiratory tract disease were highest among children aged <2 years. Hospitalizations associated with culture-positive influenza occurred at an annual rate of 3–4 per 1000 children aged <2 years. Influenza is associated with substantial morbidity in otherwise healthy children aged <5 years